A Training of Trainers (ToT) Program for Transforming Learning through Technology: Disseminating Digital Media and AI Implementation Competencies at SMAS Immim - A. Muh. Nurul Akbar; Nur Insani Amir; Nurdzakirah Amir; Arafah Nurfadillah; Wahdaniar (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service program addressed the pressing need to equip educators at SMAS Immim with the competencies to integrate digital technology and Artificial Intelligence (AI) into their teaching practices, aligning with 21st-century educational demands. The program’s focus was a comprehensive Training of Trainers (ToT) designed to empower teachers as agents of change within their school. The intervention was conducted in two core sessions. The first session involved socialization and counseling on the conceptual use of AI in education. The second, main session was an intensive, hands-on ToT workshop. It combined a crucial mindset shift using the TPACK framework with practical training in creating interactive visual media (using Canva and Genially) and critically leveraging AI tools (like ChatGPT and Gemini) for lesson planning within the Kurikulum Merdeka structure. Evaluation through pre- and post-tests revealed a significant knowledge increase, with the average score rising from 58.7 to 86.2. The program successfully enhanced participants' practical skills in digital design and AI-aided pedagogy. More importantly, it fostered a critical, adaptive mindset, enabling educators to transform their learning environments effectively. This initiative has laid a strong foundation for sustainable digital innovation at SMAS Immim.